2014
DOI: 10.1182/blood-2014-01-549022
|View full text |Cite
|
Sign up to set email alerts
|

A TCR-mimic antibody to WT1 bypasses tyrosine kinase inhibitor resistance in human BCR-ABL+ leukemias

Abstract: Key Points This study shows the effective anticancer activity of a T-cell receptor mimic antibody targeting WT1 in resistant human Ph+ ALL. In combination with tyrosine kinase inhibitors, ESKM can result in cure of Ph+ ALL in murine models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…LAAs such as WT1, PRAME, PR3, and BMI-1 in CML patients represent attractive targets for immunotherapy, [23][24][25][26][27][28][29] with efficacy demonstrated in vaccination, including dendritic cell vaccination, [30][31][32][33] and, more recently, T-cell receptor-mimic antibodies. [34][35][36] In support of these studies, we observed maximal restoration of immune recovery, as demonstrated by increased effector NK cell and T-cell immune responses, reduced PD-1 inhibitory molecule expression on CD4 1 and CD8 1 T cells, and reduced numbers of Mo-MDSC in MR 4.5 only, suggesting DMR may be the preferred threshold for future TFR studies to benefit from the improved effector immune responses. Therapeutic methods to enhance NK cell function and immunogenic CTL responses early or blocking aberrant PD-1 signaling may result in greater rate of success in TKI cessation studies.…”
Section: Discussionsupporting
confidence: 56%
“…LAAs such as WT1, PRAME, PR3, and BMI-1 in CML patients represent attractive targets for immunotherapy, [23][24][25][26][27][28][29] with efficacy demonstrated in vaccination, including dendritic cell vaccination, [30][31][32][33] and, more recently, T-cell receptor-mimic antibodies. [34][35][36] In support of these studies, we observed maximal restoration of immune recovery, as demonstrated by increased effector NK cell and T-cell immune responses, reduced PD-1 inhibitory molecule expression on CD4 1 and CD8 1 T cells, and reduced numbers of Mo-MDSC in MR 4.5 only, suggesting DMR may be the preferred threshold for future TFR studies to benefit from the improved effector immune responses. Therapeutic methods to enhance NK cell function and immunogenic CTL responses early or blocking aberrant PD-1 signaling may result in greater rate of success in TKI cessation studies.…”
Section: Discussionsupporting
confidence: 56%
“…29 This was confirmed by repeated BV173 harvests after 3 to 5 weeks of ESKM therapy. SET2 cells harvested from mouse BM likewise did not down regulate the target antigen as measured by flow cytometry (Figs.…”
Section: Selection Of Germline or Epigenetic Durable Resistance In VImentioning
confidence: 60%
“…BV173 is a Philadelphia positive ALL cell line, whose growth and response to therapy with both TCRm and tyrosine kinase inhibitors (TKIs) was previously described. 29 Lymphomatous relapse, in addition to bone marrow (BM) relapse, was frequently observed with this cell line after mAb therapy in NSG mouse models. Histologic analysis with immunohistochemical staining (IHC) of this leukemia confirmed that BV173 grows in clusters (Figs.…”
Section: In Vivo Leukemia Growth Patternsmentioning
confidence: 99%
See 2 more Smart Citations